2018
DOI: 10.1080/20440243.2018.1431031
|View full text |Cite
|
Sign up to set email alerts
|

‘What’s on your mind?’ The only necessary question in spiritual care

Abstract: Around the world, chaplains provide specialist spiritual care for people with complex healthcare needs. If the nature of chaplain interventions was better understood then multidisciplinary colleagues could both improve their own skills in spiritual care and better understand when to refer people to chaplains. A survey was constructed to establish what aspects of the chaplain/ patient relationship were most important for patients in Scotland and Australia. Outcomes were measured with the Scottish Patient Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The ‘Factor 1(F1): assessment and implementation of spiritual care’ refers to the ability to determine a patient's spiritual needs or problems and to the planning of spiritual care (ISPEC, 2019; van Leeuwen et al, 2009). For this competence, written intra‐ and interprofessional communication skills regarding spiritual needs and spiritual care are required (Snowden et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘Factor 1(F1): assessment and implementation of spiritual care’ refers to the ability to determine a patient's spiritual needs or problems and to the planning of spiritual care (ISPEC, 2019; van Leeuwen et al, 2009). For this competence, written intra‐ and interprofessional communication skills regarding spiritual needs and spiritual care are required (Snowden et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These results can be interpreted as suggesting the need to educate nurses on how to hold in‐depth conversations and interactions with patients and how to provide appropriate documentation and/or interdisciplinary sharing to promote continuity of care. Snowden et al (2018) suggested that spiritual care professionals make a difference through diagnosis, interventions, and outcomes as reported by patients. They need to be trained to listen for spiritual needs and resources of patients’ loved ones.…”
Section: Discussionmentioning
confidence: 99%
“…Curative treatments should focus on helping older adults deal with their depressive feelings and religious doubts; for instance, by improving the pastoral activity in a nursing home. Having the feeling to be able to talk about what one has on his mind turned out to be a central aspect of pastoral interventions, besides being listened to and understood as well as having religious beliefs valued (Snowden et al, 2018). In addition, trained religious professionals can open the way for religious psychotherapeutic interventions such as religious cognitive-behavioral therapy in which a biblical approach can be applied along with the education of coping strategies to deal with both the depressive feelings and the religious doubts (Dein, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This ‘unconditional positive regard’ is a well‐known Rogerian principle (Amadi, 2013). Helping people to be able to talk about what is on their mind, whatever that may be, is a central tenet of expert spiritual care (Snowden et al., 2018), so the importance of an empathic BCP should not be underestimated here.…”
Section: Discussionmentioning
confidence: 99%